Vesicoureteral reflux: Endoscopic therapy and impact on health related quality of life - Garge, Saurabh (Medknow Publications & Media Pvt Ltd, 2013)
AIM: To evaluate the health related quality of life (HRQOL) after endoscopic injection treatment for vesico ureteral reflux (VUR) in children. MATERIALS AND METHODS: Fifty four children received treatment and were prospectively evaluated for their quality of life scores, according to resolution of reflux on cystograms and status of renal scars. RESULTS: Of the 81 refluxing units, 72 (89%) had resolution of reflux whereas 9 (11%) did not resolve. The total average QOL was higher for the patients in the resolved group as compared to the non resolved group. Comparison of pre and post procedure renal DMSA scans in 44 patients showed status quo in 26, regression of scars in six, progression in two and formation of new scars in 6. The total increase in HRQOL was highest in regression group (67.91), and lowest in progression group (36.45). CONCLUSIONS: Successful endoscopic treatment of VUR is associated with improved quality of life, as indicated by higher HRQOL scores in the resolved group.